2015
DOI: 10.1080/21505594.2015.1021540
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged pre-incubation increases the susceptibility of Galleria mellonella larvae to bacterial and fungal infection

Abstract: Galleria mellonella larvae are widely used for assessing the virulence of microbial pathogens and for measuring the in vivo activity of antimicrobial agents and produce results comparable to those that can be obtained using mammals. The aim of the work described here was to ascertain the effect of pre-incubation at 15°C for 1, 3, 6 or 10 weeks on the susceptibility of larvae to infection with Candida albicans and Staphylococcus aureus. Larvae infected with C. albicans after 1 week pre-incubation at 15°C showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 43 publications
(50 reference statements)
4
36
4
1
Order By: Relevance
“…Upon arrival the larvae were stored in the dark in wood shavings at 17°C and allowed to acclimatize for at least 2 days to control for the adverse physiological consequences of shipping [27]. G. mellonella larvae were used within 1 week due to the known physiological consequences of long-term storage of larvae [30]. Healthy G. mellonella larvae were selected by weight (175-225 mg), uniformity in color (little to no melanization), and responsiveness to touch.…”
Section: Methodsmentioning
confidence: 99%
“…Upon arrival the larvae were stored in the dark in wood shavings at 17°C and allowed to acclimatize for at least 2 days to control for the adverse physiological consequences of shipping [27]. G. mellonella larvae were used within 1 week due to the known physiological consequences of long-term storage of larvae [30]. Healthy G. mellonella larvae were selected by weight (175-225 mg), uniformity in color (little to no melanization), and responsiveness to touch.…”
Section: Methodsmentioning
confidence: 99%
“…In these instances, immune priming offers short-term protection to larvae. Browne et al [53] found that when the larvae of G. mellonella were incubated at 30°C or 37°C for 72 h, they showed decreased survival compared to larvae exposed to the same conditions for a shorter period of time (24 h) prior to infection [53]. The density of hemocyte populations and the level of AMPs reached a peak at 24 h and then declined as the cost and maintenance of the primed response may outweigh its benefits.…”
Section: Thermal and Physical Stress As Immune Priming Agentsmentioning
confidence: 99%
“…9 In this edition of Virulence, the Kavanagh group report that larvae become increasingly susceptible to infection by pathogens as laboratory storage time increases, highlighting the need to consider this parameter when using the G. mellonella model. Browne et al 10 elaborate further in the study and relate this observation to a reduction in the total abundance of haemocytes that function in immune defense against pathogens and changes in the relative flux of metabolic pathways. Interestingly, the number of haemocytes after 3 weeks of incubation was approximately half that compared to the population at one week, while qualitative changes in the relative abundance of the various types of haemocytes were also reported.…”
mentioning
confidence: 92%
“…Interestingly, the number of haemocytes after 3 weeks of incubation was approximately half that compared to the population at one week, while qualitative changes in the relative abundance of the various types of haemocytes were also reported. 10 Both these factors probably contribute to reduced immune capacity and thus increased susceptibility to infection. The Browne et al study 10 and other related works raise awareness of ways to reduce inter-experimental variability and may help to standardise methods and permit more meaningful comparisons between certain types of experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation